Extracellular galectins as controllers of cytokines in hematological cancer - Gordon-Alonso, Monica (Blood, 2018)
Galectins and cytokines are both secreted proteins whose levels are prognosis factors for several cancers. Extracellular galectins bind to the glycans decorating glycoproteins and are overproduced in most cancers. Accumulative evidence shows that galectins regulate cytokines during cancer progression. Although galectins alter cytokine function by binding to the glycans decorating cytokines or their receptors, cytokines could also regulate galectin expression and function. This review revises these complex interactions and their clinical impact, particularly in hematological cancers.